2016
DOI: 10.1111/pan.13013
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal insufficiency in neonates after cardiac surgery with cardiopulmonary bypass

Abstract: Neonatal cardiac surgery with CPB and preoperative methylprednisolone leads to AI as determined by low-dose ACTH stimulation test in one-third of patients. AI is associated with increased serum lactate and colloid resuscitation in OR. Impact of preoperative methylprednisolone on results is not defined. Benefit of postoperative steroid administration in neonates with post-CPB AI warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…We did not specifically identify patients that had received cardiopulmonary bypass therapy. As for postoperative RAI, a recent study found that using a low-dose CSS (1 µg cosyntropin), investigators noted that 1/3 of neonates undergoing cardiac surgery developed RAI after surgery (based on a cutoff of +9 µg/dL change) [22]; however, these patients had received methylprednisolone prior to the CSS in preparation for the cardiopulmonary bypass. Thus, these patients may have had their hypothalamic-pituitary-adrenal axis iatrogenically suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…We did not specifically identify patients that had received cardiopulmonary bypass therapy. As for postoperative RAI, a recent study found that using a low-dose CSS (1 µg cosyntropin), investigators noted that 1/3 of neonates undergoing cardiac surgery developed RAI after surgery (based on a cutoff of +9 µg/dL change) [22]; however, these patients had received methylprednisolone prior to the CSS in preparation for the cardiopulmonary bypass. Thus, these patients may have had their hypothalamic-pituitary-adrenal axis iatrogenically suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…Only the patients diagnosed with adrenal insufficiency exhibited a significant increase in mean blood pressure and urine output in response to hydrocortisone administration [ 59 ]. A recent study by Crawford et al [ 57 ] aimed to correlate relative adrenal insufficiency to clinical outcomes in 40 neonates undergoing complex heart surgery. Like the studies discussed above, all patients received preoperative methylprednisolone.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the complexity of open-heart surgery, the processes of CPB and circulatory arrest require relatively long time periods, during which the blood supply may become blocked, leading to myocardial ischemia and hypoxia ( 31 ). After the aorta is opened, the heart is re-perfused with systemic blood flow and a large number of white blood cells accumulate in the myocardial microvascular bed and interact with inflammatory mediators, resulting in the release of oxygen free radicals and other toxic substances, which ultimately leads to ischemic injury and an enhanced systemic inflammatory response ( 8 , 32 ). Accordingly, these events increase the incidence of postoperative malignant arrhythmia and low cardiac output syndrome.…”
Section: Discussionmentioning
confidence: 99%